Optimal limb regeneration strategies in Hemigrapsus sanguineus - Fletcher, Laura S.; Griffen, Blaine D. (Frontiers in Ecology and Evolution, 2024)
Non-lethal injury in animals is both common and costly. The cost of regenerating autotomized limbs may leave less energy available for processes such as reproduction and growth, leading to trade-offs. Such trade-offs are context-dependent, and an individual’s energy allocation strategies may vary widely based on its condition and the environment. However, many traditional bioenergetics models have relied on fixed energy allocation rules, such as the -rule of dynamic energy budget theory, which assumes a fixed proportion (κ) of assimilated energy is always allocated to growth and maintenance. To determine whether incorporating optimality approaches into bioenergetics models improves the ability to predict energy allocation, we developed a dynamic state variable model that identifies optimal limb regeneration strategies in a model system, the Asian shore crab Hemigrapsus sanguineus. Our model predictions align with known patterns for this species, including increased regeneration effort with injury severity, a shift from reproduction to growth as consumption amount increases, and an increase in regeneration effort as regeneration progresses. Lastly, Monte Carlo simulations of individuals from a previous experiment demonstrate that flexible energy allocation successfully predicts reproductive effort, suggesting that this approach may improve the accuracy of bioenergetics modeling.